Economic Crisis and its Impact on Promotion and Media in Cyprus. (2nd September 2016) - Papasolomou, Ioanna; Kitchen, Philip J.; Panopoulos, Anastasios; Sabova, Maria
ABSTRACT: The economic crisis has redounded sharply upon marketing communications and media vehicles in Cyprus. In recession periods, communication and marketing budgets can contract while companies seek to obtain the best communication outcomes with more limited resources, both the size and the distribution of the communication mix can alter rapidly. This qualitative paper reveals that Cypriot advertising agencies now place greater emphasis upon marketing public relations (MPR) as it is perceived to be cost effective and efficient in achieving campaign objectives. The empirical data also indicates a shift towards the use of internet marketing and social media as more and more businesses are realizing the importance of consumer generated marketing and word-of-mouth/mouse marketing (WOMm).